Application of clinical and molecular profiling data to improve patient outcomes in psoriatic arthritis - FitzGerald, O; Behrens, F; Barton, A; Bertheussen, H; Boutouyrie-Dumont, B; Coates, L; Davies, O; de Wit, M; Fagni, F; Goodyear, CS; Gurke, R; Hahnfeld, L; et al. (SAGE Publications, 2023)
Achieving a good outcome for a person with Psoriatic Arthritis (PsA) is made difficult by late diagnosis, heterogenous clinical disease expression and in many cases, failure to adequately suppress inflammatory disease features. Single-centre studies have certainly contributed to our understanding of disease pathogenesis, but to adequately address the major areas of unmet need, multi-partner, collaborative research programmes are now required. HIPPOCRATES is a 5-year, Innovative Medicines Initiative (IMI) programme which includes 17 European academic centres experienced in PsA research, 5 pharmaceutical industry partners, 3 small-/medium-sized industry partners and 2 patient-representative organizations. In this review, the ambitious programme of work to be undertaken by HIPPOCRATES is outlined and common approaches and challenges are identified. It is expected that, when completed, the results will ultimately allow for changes in the approaches to diagnosing, managing and treating PsA allowing for better short-term and long-term outcomes.